2008
DOI: 10.1016/j.jpag.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Collected Vaginal Swab, First Void Urine, and Endocervical Swab Specimens for the Detection of Chlamydia Trachomatis and Neisseria Gonorrhoeae in Adolescent Females

Abstract: OBJECTIVE-To assess the concordance of self-obtained vaginal swabs (SVS), first void urine samples (FVU) and provider-collected endocervical swabs (PES) for the detection of chlamydia trachomatis (CT) and neisseria gonorrrhoeae (NG) in adolescents.METHODS-A total of 342 adolescent women and 1,080 baseline and semi-annual visits were analyzed. FVU, SVS and PES were collected at each biannual visit. All specimens were tested by BDProbeTec ET ™ Amplified DNA Assay. Sensitivity, specificity, positive predictive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 13 publications
1
63
0
1
Order By: Relevance
“…Thoughtfully developed programs that allow appropriately selected patients or parents and other caregivers to collect throat swabs without requiring a health care visit can limit patient exposure to other sick individuals, improve health care access, increase convenience, and decrease reliance on more costly health care options such as evening urgent care clinics or emergency departments, while still restricting antibiotic use to patients with a positive GAS test result. Our findings are in keeping with those of other studies that have demonstrated success with self-swab collection options, such as influenza testing from midnasal turbinate specimens (17), sexually transmitted infection testing from vaginal swabs (18,19), and molecular testing of samples from buccal swabs (20,21), and provide the foundation for implementation of GAS self-swab programs.…”
Section: Discussionsupporting
confidence: 88%
“…Thoughtfully developed programs that allow appropriately selected patients or parents and other caregivers to collect throat swabs without requiring a health care visit can limit patient exposure to other sick individuals, improve health care access, increase convenience, and decrease reliance on more costly health care options such as evening urgent care clinics or emergency departments, while still restricting antibiotic use to patients with a positive GAS test result. Our findings are in keeping with those of other studies that have demonstrated success with self-swab collection options, such as influenza testing from midnasal turbinate specimens (17), sexually transmitted infection testing from vaginal swabs (18,19), and molecular testing of samples from buccal swabs (20,21), and provide the foundation for implementation of GAS self-swab programs.…”
Section: Discussionsupporting
confidence: 88%
“…Others have examined strategies such as selfcollection (non-invasive samples) [1][2][3][4][5][6][7][8] and point-of-care (POC) tests to improve the diagnosis of STIs. [9][10][11][12] Self-collection may be advantageous for women who dislike pelvic examinations or in settings where providers cannot perform pelvic examinations.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether adolescents prefer self or clinician testing for trichomoniasis, which factors predict acceptability of self-testing, and whether acceptability of self-testing improves after performing the test. Thus we designed a study with the following aims: (1) to validate a scale to measure acceptability of self and clinician testing for trichomoniasis; (2) to compare the preferences for and acceptability of self versus clinician testing for STIs using a simple POC test for trichomoniasis; (3) to examine how acceptability changes after experience with testing and review of test results; and (4) to examine whether acceptability is associated with sociodemographic, behavioural or gynaecological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Las especificidades oscilaron entre 94,7 y 99,7 % para ambos microorganismos. Se calculó el coeficiente kappa para evaluar la concordancia entre dos combinaciones diferentes de los tres tipos de espécimen, considerándola excelente si dicho coeficiente era mayor de 0,75, y se registraron valores superiores a este (p<0,0001) en todos los casos (18).…”
unclassified